PEMBELAJARAN EVOLUSI BERBANTUAN PRAKTIKUM VIRTUAL DALAM MENGEMBANGKAN BERPIKIR KRITIS DAN SIKAP ILMIAH PADA MAHASISWA CALON GURU - Fitriani, Irfani (2012)
The aim of this research is to analyze the increase of disposition and ability of critical thinking, scientific attitudes, and concept comprehension of preservice biology teacher through the evolution learning assisted by virtual laboratory. The participants in this weak experiment study using the one group pretest-posttest design were 72 preservice biology teachers at Indonesia University of Education. The results of statistical analysis showed that the evolution learning assisted by virtual laboratory enhance the ability of critical thinking (0.30) and concept comprehension of the "mechanism of evolution" (0.35) with average N-gain are medium categories, the disposition of critical thinking (0.20) and scientific attitudes (0.18) are low categories. The evolution learning assisted by virtual laboratory enhance every indicators that was studied with average N-gain are medium categories: truth-seeking (0.35), self confident (0.38), asking and answering question of clarification and challenge (0.32), inducing and judging inductions (0.33), deciding on an action (0.51), taking a positive attitude to failure (0.35), and understand categories of the cognitive process dimension (0.40) with factual knowledge dimension (0.37). The result of questionnaire showed 81% preservice teacher stated that the virtual laboratory of evolution are interesting and clear enough to follow, so that it hope to be used in the next lectures. Keywords: Evolution learning, virtual laboratory, disposition and ability of critical thinking, scientific attitudes, concept comprehension of the mechanism of evolution